Working List of Networking Sites (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2012)
This is a working list of prior learning assessment-related networking sites.  We invite you to email any suggestions to PLAInsideOut@esc.edu.